Is gambling an emerging public health issue in Wales, UK? An assimilation of literature and data. (November 2018) - Beynon, Claire; Atherton, Frank
Abstract: Background: Harm from gambling is found at individual, social, and community levels, and includes financial hardship, psychological distress, and interpersonal conflict or relationship breakdown. The harm from gambling to wider society includes fraud, theft, loss of productivity, and the cost of treatment. We aimed to assess whether gambling is an emerging public health problem in Wales. Methods: We reviewed existing data sources (such as surveys and tax receipts for the past 10 years) and literature (for 2014–17, using a search conducted on "problem gambling" by the Welsh Government Library Service) to ascertain the impact of gambling in Wales with respect to four key public health concepts: cost to society, preventability, inequalities in society, and need for population level interventions. Multiple academics, third sector organisations, and statutory bodies were engaged in informing this study. Findings: In Wales, 61% of adults had gambled in 2016 (1·5 million people) and 1·1% of the population (30 000 people) self-reported as having a problem with gambling. The annual estimated excess cost of gambling for Wales was between £40 million and £70 million, which is a substantial cost to society. People categorised as most deprived were more likely than those in the least deprived category to bet more than they can afford, to have experienced financial problems caused by gambling, and to classify themselves as problem gamblers. We found that gambling harm can be limited by use of evidence-based interventions from international best practice; the characteristics that they must combine are multiple, coordinated population-level interventions implemented over a sustained period of time. Interpretation: Our study provides a picture of the rapidly evolving developments and infrastructure that make gambling an emerging public health issue in Wales. The public health approach aims to improve quality of life and to achieve health equity. This focus on equity is necessary since people living in areas of deprivation are more likely to experience gambling-related harm. Public health action to reduce harm from gambling should include numerous population-based measures. Funding: None.